2000
DOI: 10.1001/archsurg.135.10.1137
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Laparoscopic Splenectomy

Abstract: Hypothesis: Analysis of the type and characteristics of complications after laparoscopic splenectomy may permit the identification of clinical factors with predictive value for the development of complications. Design: Univariate and multivariate analysis of factors related to complications in a prospective series of laparoscopic splenectomies. Setting: A large tertiary referral university-teaching general hospital. Patients: One hundred twenty-two nonselected consecutive patients, in whom laparoscopic splenec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 16 publications
3
27
0
4
Order By: Relevance
“…In Winslow's meta-analysis haemorrhage was described in 4.8% of patients, including the need for conversion for intraoperative bleeding and 1.6% if conversions were excluded [30]. Other authors mentioned above report a hemorrhagic complication rate of 0 to 5.5% [8,12,16,17,22,29,33,34]. In our group two patients (2.59%) needed conversion to open procedure.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In Winslow's meta-analysis haemorrhage was described in 4.8% of patients, including the need for conversion for intraoperative bleeding and 1.6% if conversions were excluded [30]. Other authors mentioned above report a hemorrhagic complication rate of 0 to 5.5% [8,12,16,17,22,29,33,34]. In our group two patients (2.59%) needed conversion to open procedure.…”
Section: Discussionmentioning
confidence: 51%
“…We have studied the number of adverse events. An adverse event was any deviation from ideal postoperative course [3,8], hence their high rate (12.98%). However, only 3 events in this group were related to surgical technique (3.89% of the study population).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Targorona et al, the mean operative time and length of hospital stay for LS was reported as 153 minutes and four days, respectively for a total of 113 cases. 23 In another study by Rescorla et al, the mean hospital stay was reported as 1.4 days and the means operative time was found as 115 minutes. 18 In a recent study by Deng et al, 57 pediatric cases with LS were analyzed and it was reported that the mean length for hospital stay was five days and the mean operative time was 120 minutes.…”
Section: Discussionmentioning
confidence: 92%
“…En un estudio de Targarona y col., se informó que la duración media de la cirugía y de la hospitalización con la EL fue de 153 minutos y cuatro días, respectivamente, en un total de 113 pacientes. 23 En otro estudio de Rescorla y col., se informó que la media de hospitalización fue de 1,4 días y la media de la duración de la cirugía fue de 115 minutos. 18 En un estudio reciente de Deng y col., se analizaron 57 pacientes pediátricos con EL y se informó que la duración media de la hospitalización fue de cinco días y de la cirugía, de 120 minutos.…”
Section: Discussionunclassified